2002
DOI: 10.1113/jphysiol.2001.020180
|View full text |Cite
|
Sign up to set email alerts
|

Localization of aquaporin‐5 in sweat glands and functional analysis using knockout mice

Abstract: Sweat secretion involves the transport of salt and water into the lumen of the secretory coil of the sweat gland. By analogy to salivary and submucosal glands, where fluid secretion is aquaporin‐5 (AQP5) dependent, we postulated that aquaporin water channels might facilitate sweat secretion. Immunolocalization with specific antibodies revealed strong expression of AQP5 at the luminal membrane of secretory epithelial cells in sweat glands in mouse paw skin. Novel quantitative methods were developed to compare s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
76
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 34 publications
9
76
1
Order By: Relevance
“…In each of these systems the rate of transepithelial fluid secretion normalized to epithelial surface area is very high, such that the reduced but non-zero water permeability in AQP deficiency impairs transepithelial osmotic equilibration. In other epithelia, where areanormalized rates of fluid absorption/secretion are much lower, AQPs are not required for transepithelial fluid transport, as found for tear fluid secretion by lacrimal gland , sweat secretion (Song et al, 2002), alveolar fluid absorption (Bai et al, 1999;, and airway fluid absorption . Involvement of AQP-in the reduced tear fluid secretion in Sjogren's syndrome has been suggested (Tsubota et al, 2001), though subsequently refuted (Beroukas et al, 2001).…”
Section: Aqp Roles Related To Aqp-facilitated Water Transportmentioning
confidence: 97%
“…In each of these systems the rate of transepithelial fluid secretion normalized to epithelial surface area is very high, such that the reduced but non-zero water permeability in AQP deficiency impairs transepithelial osmotic equilibration. In other epithelia, where areanormalized rates of fluid absorption/secretion are much lower, AQPs are not required for transepithelial fluid transport, as found for tear fluid secretion by lacrimal gland , sweat secretion (Song et al, 2002), alveolar fluid absorption (Bai et al, 1999;, and airway fluid absorption . Involvement of AQP-in the reduced tear fluid secretion in Sjogren's syndrome has been suggested (Tsubota et al, 2001), though subsequently refuted (Beroukas et al, 2001).…”
Section: Aqp Roles Related To Aqp-facilitated Water Transportmentioning
confidence: 97%
“…This is particularly clear with mutations in connexins, whereby recessive loss-offunction mutations underlie non-syndromic deafness in the absence of an associated skin phenotype (Scott and Kelsell, 2011). This might also be the case for AQP5, as AQP5-null mice have no reported skin abnormalities (Song et al, 2002), although the anatomy of the skin has not been directly studied in these mice. However, mice lacking TRPV3 expression in keratinocytes exhibit a significantly thinner stratum corneum, altered keratinocyte differentiation and impaired barrier function (Cheng et al, 2010), whereas AQP3-null mice retain normal barrier function, but display delayed barrier recovery after disruption .…”
Section: Perspectivesmentioning
confidence: 98%
“…Until recently, the expression of AQP5 in the skin was believed to be restricted to the sweat gland cells in the dermis, although its role in sweat secretion is not clear (Nejsum et al, 2002;Song et al, 2002;Inoue et al, 2013). However, we have recently reported the first inherited skin disease associated with aquaporin mutations and have shown that AQP5 is expressed throughout the epidermis, albeit at a much lower level than seen in the sweat glands, with a particularly strong localisation at the plasma membrane in keratinocytes of the stratum granulosum of the palmar epidermis (Fig.…”
Section: Aqp5mentioning
confidence: 99%
“…In the various epithelia mentioned above the rates of transepithelial fluid secretion normalized to epithelial surface area are very high, such that the reduced water permeability in AQP deficiency impairs transepithelial osmotic equilibration. In other epithelia having much lower rates of fluid absorption or secretion, including lacrimal gland , sweat gland (Song et al, 2002), alveolus (Bai et al, 1999;Ma et al, 2000a), and airways , AQP deletion does not impair transepithelial fluid transport. Transepithelial water transport is not rate limiting for fluid secretion when rates of fluid secretion are low.…”
Section: Functions Of Aquaporins In Cell and Organ Physiology Anticipmentioning
confidence: 99%